2015
DOI: 10.1021/acsinfecdis.5b00081
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Sterol Isolated from a Plant Used by Mayan Traditional Healers Is Effective in Treatment of Visceral Leishmaniasis Caused by Leishmania donovani

Abstract: *Corresponding Author: Phone: (614) .edu. Δ Author Contributions: G.G., K.J.P., and D.A. contributed equally to this work Supporting Information The Supporting Information is available free of charge on the ACS Publications website at DOI: 10.1021/acsinfecdis.5b00081. Procedures and spectral data for the stepwise synthesis of pentalinonsterol (PDF) NotesThe authors declare no competing financial interest. HHS Public AccessAuthor manuscript ACS Infect Dis. Author manuscript; available in PMC 2017 December 15.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 61 publications
(108 reference statements)
0
11
0
Order By: Relevance
“…B.F.Hansen & Wunderlin, was active on promastigote forms of L. (L.) mexicana in vitro ( Lezama-Dávila et al, 2007 ) and BALB/c mice infected with L. (L.) mexicana treated with 10 μg of this extract by the topical route, once a day for six weeks, presented fewer parasites in the skin; in addition, treated animals produced high levels of IL-12 cytokine along with the expression of the costimulatory molecules CD40, CD80, and CD86 ( Lezama-Dávila et al, 2014 ), suggesting that, at least in part, the leishmanicidal activity in vivo may be associated with stimulation of innate immune cells. Further studies led to the identification of sterols from the roots of this plant that were active on intracellular amastigote forms of L. (L.) mexicana with an IC 50 between 0.03 and 14.5 μM ( Pan et al, 2012 ) , and the sterol pentalinonsterol encapsulated in liposomes, given by the intravenous route at 2.5 mg/kg, significantly reduced the number of viable parasites in the liver, spleen and bone marrow of BALB/c mice infected with L. (L.) donovani ; additionally, this molecule activated the Th1 immune response in treated animals ( Gupta et al, 2015 ). The genus Aspidospermum has been cited as a source of natural medicine against leishmaniasis, and bioactive alkaloids purified from different species of this genus may be responsible for the efficacy of plants observed in traditional communities ( Tanaka et al, 2007 ; Reina et al, 2014 ); however, studies involving experimental models of leishmaniasis ( in vivo ) have not been performed thus far.…”
Section: Plants Recommended For the Treatment Of Leishmaniasis By Traditional Communities Worldwidementioning
confidence: 99%
“…B.F.Hansen & Wunderlin, was active on promastigote forms of L. (L.) mexicana in vitro ( Lezama-Dávila et al, 2007 ) and BALB/c mice infected with L. (L.) mexicana treated with 10 μg of this extract by the topical route, once a day for six weeks, presented fewer parasites in the skin; in addition, treated animals produced high levels of IL-12 cytokine along with the expression of the costimulatory molecules CD40, CD80, and CD86 ( Lezama-Dávila et al, 2014 ), suggesting that, at least in part, the leishmanicidal activity in vivo may be associated with stimulation of innate immune cells. Further studies led to the identification of sterols from the roots of this plant that were active on intracellular amastigote forms of L. (L.) mexicana with an IC 50 between 0.03 and 14.5 μM ( Pan et al, 2012 ) , and the sterol pentalinonsterol encapsulated in liposomes, given by the intravenous route at 2.5 mg/kg, significantly reduced the number of viable parasites in the liver, spleen and bone marrow of BALB/c mice infected with L. (L.) donovani ; additionally, this molecule activated the Th1 immune response in treated animals ( Gupta et al, 2015 ). The genus Aspidospermum has been cited as a source of natural medicine against leishmaniasis, and bioactive alkaloids purified from different species of this genus may be responsible for the efficacy of plants observed in traditional communities ( Tanaka et al, 2007 ; Reina et al, 2014 ); however, studies involving experimental models of leishmaniasis ( in vivo ) have not been performed thus far.…”
Section: Plants Recommended For the Treatment Of Leishmaniasis By Traditional Communities Worldwidementioning
confidence: 99%
“…In mice immunized with OVA, the administration of pentalinonsterol increased the level of antibodies in the serum; meanwhile, splenocytes and lymph node cells isolated from treated mice secreted more cytokines, such as IFN-γ and IL-10, when compared with the control group [ 111 ]. In a study by Gupta, pentalinonsterol treatment to combat parasites was found to induce T cell proliferation and cytokine release [ 84 ]. The immunostimulatory effects of Andrographis paniculata extract and andrographolide ( Figure 9 ) were tested in vitro and in vivo.…”
Section: Natural Products That Enhance Immunitymentioning
confidence: 99%
“…Intracellular parasitic load can be determined by staining infected cells with Giemsa stain, wherein the parasites will significantly take up the stain above background. Alternatively, fluorescently labeled Leishmania - or luciferase-expressing parasites can be used spectrometrically to obtain intracellular parasite count . Promastigotes or axenic amastigotes can also be grown in suspension and treated with the drug formulation to evaluate the direct effects of the formulations on the parasite.…”
Section: Experimental Models Of Vlmentioning
confidence: 99%